Negative electrode slurry, negative electrode plate and battery

By using specific dispersants in the negative electrode slurry, the problem of poor stability of the negative electrode slurry is solved, and the energy density and circulation performance of the battery are significantly improved.

CN119725537AActive Publication Date: 2025-03-28EVE ENERGY CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411899612.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The negative electrode slurry has poor stability, resulting in poor battery energy density and circulation performance.

Method used

A negative electrode slurry including dodecylsulfosuccinate, castor oil sulfate, styrene-custardic anhydride and other dispersants is used to ensure uniform distribution of each substance and stable viscosity.

Benefits of technology

It improves the stability and rheological performance of the negative electrode slurry, improves the energy density and cycling performance of the battery, and ensures the stable performance of the battery during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203935160000161
    Figure BDA0005203935160000161
  • Figure BDA0005203935160000171
    Figure BDA0005203935160000171
  • Figure BDA0005203935160000172
    Figure BDA0005203935160000172
Patent Text Reader

Abstract

The invention provides negative electrode slurry, a negative electrode plate and a battery, and relates to the technical field of lithium ion batteries, the negative electrode slurry comprises a negative electrode active material, a conductive agent, a binder and a dispersant; the dispersing agent is prepared from at least one of dodecyl sulfosuccinate, castor oil sulfate, lauryl sulfate, butyl oleate sulfate, alkyl pyridinium chloride, polyoxyhexene alkyl ether, acetylene glycol, dialkyl sulfosuccinate, polycarboxylate, a polymethacrylic acid derivative, styrene-maleic anhydride and condensed naphthalene sulfonate. When the negative electrode plate containing the negative electrode slurry is applied to the battery, the energy density and the cycle performance of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode slurry, a negative electrode sheet and a battery. Background Art

[0002] The negative electrode sheet is one of the key components of lithium-ion batteries, and its performance directly affects the overall electrochemical performance of lithium-ion batteries. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer on the surface of the negative electrode current collector. The negative electrode active layer is coated with a negative electrode slurry formed by negative electrode active materials, conductive agents, binders and solvents. Due to the presence of a large number of chemical substances and nano-scale particles in the negative electrode slurry, the negative electrode slurry has poor stability during processing, and the various substances are unevenly distributed in the slurry, resulting in uneven distribution of various substances on the electrode after coating, which will directly affect the energy density and cycle performance of the battery. Summary of the invention

[0003] The main purpose of the present application is to provide a negative electrode slurry, a negative electrode sheet and a battery to solve the problem in the related art that the negative electrode slurry has poor stability and affects the battery energy density and cycle performance.

[0004] In order to achieve the above-mentioned object, according to a first aspect of the present application, a negative electrode slurry is provided, the negative electrode slurry comprising a negative electrode active material, a conductive agent, a binder and a dispersant;

[0005] The dispersant includes at least one of dodecyl sulfosuccinate, castor oil sulfate, lauryl sulfate, butyl oleate sulfate, alkyl pyridinium chloride, polyoxyethylene alkyl ether, acetylene glycol, dialkyl sulfosuccinate, polycarboxylate, polymethacrylic acid derivatives, styrene-maleic anhydride, and condensed naphthalene sulfonate.

[0006] Furthermore, the molecular weight of the alkyl pyridinium chloride is 330 to 350; the dialkyl sulfosuccinate is selected from sodium dialkyl sulfosuccinate; the polycarboxylate is selected from at least one of sodium polyacrylate, polyethyl methacrylate, and calcium polyacrylate; the polymethacrylic acid derivative is selected from polymethyl methacrylate; the weight average molecular weight of styrene-maleic anhydride is 10,000 to 200,000; and the condensed naphthalene sulfonate is selected from sodium condensed naphthalene sulfonate.

[0007] Furthermore, the dispersant includes castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate, and the mass ratio of the castor oil sulfate, the styrene-maleic anhydride and dodecyl sulfosuccinate is (3-5): (3-5): (1-3).

[0008] Furthermore, the negative electrode slurry includes, by mass content, 91% to 97% of negative electrode active material, 2% to 5% of binder, 0.3% to 3% of conductive agent and 0.1% to 1.5% of dispersant.

[0009] Further, the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, graphene, silicon oxygen, and silicon carbon; and / or,

[0010] The binder includes at least one of styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, and polyimide; and / or,

[0011] The conductive agent includes at least one of conductive carbon black, conductive graphite, nano-carbon fiber, carbon nanotube, and graphene;

[0012] Preferably, the negative electrode active material includes graphite and silicon carbon, wherein the mass ratio of graphite to silicon carbon is (6-9):(1-4).

[0013] Furthermore, the initial viscosity of the negative electrode slurry is 3000-4500 mPa·s; after the negative electrode slurry is left standing for 24 hours at 25°C and ambient humidity ≤25%, the viscosity is 5000-9000 mPa·s, and the difference between the solid content of the upper layer and the solid content of the lower layer is <0.3%.

[0014] In a second aspect of the present application, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active layer formed by the negative electrode slurry provided in the first aspect.

[0015] Furthermore, the peeling force between the negative electrode current collector and the negative electrode active layer is greater than 1.2 N / m.

[0016] Further, the thickness of the negative electrode active layer is 60 to 100 μm; and / or,

[0017] The compaction density of the negative electrode active layer is 1.4-1.8 mg / cm 3 and / or,

[0018] The surface density of the negative electrode sheet is 60-300 mg / cm 2 .

[0019] A third aspect of the present application provides a battery, comprising the negative electrode sheet provided in the second aspect.

[0020] Furthermore, the battery also includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode active layer containing a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide, lithium-rich manganese, lithium nickel cobalt manganese oxide, lithium manganese oxide, and lithium iron phosphate.

[0021] By applying the technical solution of the present application and introducing a specific dispersant, the negative electrode slurry can maintain a low viscosity change and a uniform solid content distribution after standing for a long time, effectively avoiding slurry stratification, indicating that the negative electrode slurry has excellent stability, which is beneficial to improving the rheological properties and coating uniformity of the negative electrode slurry, and thus helps to improve the energy density and cycle performance of the battery. DETAILED DESCRIPTION

[0022] As described in the background of the present application, the prior art has a problem that the negative electrode slurry has poor stability and affects the battery energy density and cycle performance. In order to solve the above problems, the first aspect of the present application provides a negative electrode slurry, the negative electrode slurry includes an active material, a conductive agent, a binder and a dispersant, and the dispersant includes at least one of dodecyl sulfosuccinate, castor oil sulfate, lauryl sulfate, butyl oleate sulfate, alkyl pyridinium chloride, polyoxyethylene alkyl ether, acetylene glycol, dialkyl sulfosuccinate, polycarboxylate, polymethacrylic acid derivatives, styrene-maleic anhydride, and condensed naphthalene sulfonate.

[0023] The negative electrode slurry includes active materials, conductive agents, binders and dispersants. Dispersants are used to improve the dispersibility of various substances in the negative electrode slurry, so that after the negative electrode slurry is left to stand for 24 hours under specific conditions, the various components in the slurry can maintain a uniform distribution state. First, the active materials are evenly distributed in the slurry, and the active materials are evenly distributed on the negative electrode after coating, which can provide a more consistent electrochemical reaction environment, ensure the stability of the battery performance during the charging and discharging process, and help improve the energy density and cycle performance of the battery. Secondly, the distribution of the conductive agent in the slurry is directly related to the formation of the conductive network inside the battery electrode. The slurry is uniform and stable, and the conductive agent can be evenly dispersed, which helps to form a continuous and stable conductive network and improve the conductivity of the electrode. Good conductivity means that the electron transmission inside the battery is smoother, the charging and discharging efficiency is higher, and the power performance and energy density of the battery will also be improved; in addition, the role of the binder is to adhere the active material and the conductive agent to the negative electrode current collector, while maintaining the stability of the electrode structure, avoiding cracks or falling off during the charging and discharging process, affecting the cycle life and safety of the battery.

[0024] By selecting a specific dispersant, the present application can make the components in the negative electrode slurry evenly distributed, so that the viscosity and solid content remain stable, and the uniform stability of the negative electrode slurry is improved, thereby helping to improve the energy density and cycle performance.

[0025] In some embodiments, the molecular weight of the alkyl pyridinium chloride is 330-350; the dialkyl sulfosuccinate is selected from sodium dialkyl sulfosuccinate; the polycarboxylate is selected from at least one of sodium polyacrylate, polyethyl methacrylate, and calcium polyacrylate; the polymethacrylic acid derivative is selected from polymethyl methacrylate; the weight average molecular weight of styrene-maleic anhydride is 10,000-200,000; and the condensed naphthalene sulfonate is selected from sodium condensed naphthalene sulfonate.

[0026] In some embodiments, the dispersant includes castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate, and the mass ratio of castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate is (3-5): (3-5): (1-3). By limiting the dispersant to include castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate, the three substances are used in combination to exert a synergistic effect and improve battery performance.

[0027] Specifically, castor oil sulfate is a natural surfactant with good wettability and dispersibility. Castor oil sulfate can improve the wettability of negative electrode materials, thereby increasing the conductivity and charge-discharge performance of the battery. In addition, castor oil sulfate has excellent biodegradability and is environmentally friendly.

[0028] Styrene-maleic anhydride is a synthetic polymer material, specifically a copolymer of styrene and maleic anhydride (maleic anhydride), with a copolymerization ratio (molar ratio of styrene to maleic anhydride) of (1-4):1. Styrene-maleic anhydride has good adhesion and stability. Styrene-maleic anhydride can improve the structural stability of the negative electrode sheet, reduce volume expansion and contraction during charging and discharging, and thus extend the battery life. In addition, the adhesion properties of styrene-maleic anhydride help improve the mechanical stability of the battery.

[0029] Dodecyl sulfosuccinate is a surfactant with good dispersibility and stability. Dodecyl sulfosuccinate can improve the dispersibility of negative electrode materials and reduce particle agglomeration, thereby improving the charge and discharge efficiency of the battery. In addition, dodecyl sulfosuccinate can also improve the cycle stability and thermal stability of the battery.

[0030] When these three substances are used in combination, their advantages can complement each other: the wettability and dispersibility of castor oil sulfate and dodecyl sulfosuccinate can improve the conductivity of the negative electrode active layer; the bonding performance of styrene-maleic anhydride can improve the structural stability of the battery and reduce volume changes; dodecyl sulfosuccinate can improve the cycle stability of the battery and reduce the risk of thermal runaway, and the biodegradability of castor oil sulfate makes the entire formula more environmentally friendly.

[0031] Therefore, the present application uses castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate in a specific ratio as a dispersant for the negative electrode slurry. The combined use of these three substances can improve the energy density and cycle performance of the battery.

[0032] This application does not limit the content of each component in the negative electrode slurry, which can be adjusted according to actual needs. In some embodiments, the negative electrode slurry includes: 91% to 97% of negative electrode active material, 2% to 5% of binder, 0.3% to 3% of conductive agent and 0.1% to 1.5% of dispersant by mass content. By limiting the ratio of each substance in the negative electrode active layer, the energy density and cycle performance can be further improved.

[0033] Among them, the mass content of the negative electrode active material in the negative electrode active material layer is 91% to 97%, for example, 91%, 95%, 96%, 97% or a range consisting of any two thereof; the mass content of the binder in the negative electrode active material layer is 2% to 5%, for example, 2%, 3%, 4%, 5% or a range consisting of any two thereof; the mass content of the conductive agent in the negative electrode active material layer is 0.3% to 3%, for example, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two thereof; the mass content of the dispersant in the negative electrode active material layer is 0.1% to 1.5%, for example, 0.1%, 0.2%, 0.5%, 1%, 1.5% or a range consisting of any two thereof.

[0034] The present invention does not limit the specific types of negative electrode active materials, binders and conductive agents. For example, in some embodiments, the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, graphene, silicon oxygen, and silicon carbon; and / or the binder includes at least one of styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, and polyimide; and / or the conductive agent includes at least one of conductive carbon black, conductive graphite, nano-carbon fiber, carbon nanotubes, and graphene.

[0035] In some embodiments, the negative electrode active material includes graphite and silicon carbon. By mixing graphite and silicon carbon in a specific ratio, the specific capacity of the negative electrode can be significantly improved while ensuring a certain degree of cycle stability, thereby improving the energy density of the entire battery. The stability of graphite can also be used to mitigate the impact of silicon volume expansion and improve the cycle stability of the composite material. In addition, the overall conductive network of the negative electrode material can be improved, which helps to improve the rate performance of the battery, that is, the ability to charge and discharge quickly.

[0036] In some embodiments, the mass ratio of graphite to silicon carbon is (6-9):(1-4). By limiting the mass ratio of graphite to silicon carbon to (6-9):(1-4), the energy density and energy density of the battery can be significantly improved while maintaining a certain cycle stability and safety. Through the appropriate proportion of compounding, the high capacity advantage of silicon is brought into play, and the stability and conductivity of graphite are used to achieve a balance between performance and stability.

[0037] The mass ratio of graphite to silicon carbon is (6-9):(1-4), for example, 6:4, 7:3, 8:2, 9:1 or a range consisting of any two thereof.

[0038] In some embodiments, the initial viscosity of the negative electrode slurry is 3000-4500 mPa·s. After the negative electrode slurry is left standing for 24 hours at 25°C and ambient humidity ≤25%, the viscosity is 5000-9000 mPa·s, and the difference between the solid content of the upper layer and the solid content of the lower layer is <0.3%.

[0039] The viscosity of the negative electrode slurry will directly affect the coating performance, leveling and uniformity of the final negative electrode. The viscosity value can be understood as the viscosity of the slurry, and the size of the viscosity value is one of the indicators to measure the stability of the slurry. A lower viscosity value indicates that the negative electrode slurry has better fluidity, which helps to achieve a more uniform coating during the coating process and reduce coating defects such as dark marks, uneven granularity or foil wrinkles and pulls. At the same time, the viscosity of the slurry changes less and can remain stable for a long time, which is conducive to control and operation during the production process.

[0040] The present application limits the viscosity of the negative electrode slurry after standing for 24 hours at 25°C and ambient humidity ≤25% to 5000-9000, with the unit being "milliPascal seconds" (mPa·s). This indicates that the negative electrode slurry has a lower viscosity value and the viscosity of the negative electrode slurry changes little. The present application can effectively control the slurry viscosity, optimize the stability and processability of the slurry, and thereby improve the performance and production efficiency of the battery.

[0041] The difference between the solid content of the upper layer and the solid content of the lower layer is used to characterize the sedimentation stability of the negative electrode slurry after standing for 24 hours, and can be used to evaluate the dispersion uniformity and stability of the slurry. Specifically, sedimentation stability is a performance indicator to measure whether the active material particles are evenly distributed after the slurry is standing, and whether there is significant sedimentation or floating. After standing for a long time, the smaller the difference in solid content between the upper and lower layers, the more evenly dispersed the particles in the slurry, which can ensure the uniformity of the subsequent coating process and the consistency of battery performance. If the difference in solid content between the upper and lower layers is large, it indicates that the slurry has a certain degree of sedimentation after standing for 24 hours, resulting in a difference in the solid content of the upper and lower layers, which may affect the uniformity of the coating and the final performance of the battery.

[0042] The present application stipulates that after the negative electrode slurry is allowed to stand for 24 hours at 25°C and ambient humidity ≤25%, the difference in solid content between the upper layer and the lower layer is less than 0.3%. This means that after 24 hours of standing, the ratio of the solid content of the upper layer to the solid content of the lower layer of the slurry is very close, almost the same, which means that the sedimentation stability of the slurry is very good, the particles are evenly distributed in the slurry, and there is no obvious sedimentation or floating phenomenon, which is conducive to ensuring the long-term stability of the slurry, the uniformity of the coating process, and the performance consistency of the final battery electrode.

[0043] Therefore, the present application limits the viscosity of the negative electrode slurry to 5000-9000 mPa·s after standing for 24 hours at 25°C and ambient humidity ≤25%, and the difference between the solid content of the upper layer and the solid content of the lower layer is less than 0.3%, so that the negative electrode slurry can maintain a low viscosity change and uniform solid content distribution after standing for a long time, and the various components in the negative electrode slurry can remain in a uniformly distributed state, effectively avoiding slurry stratification, ensuring that the negative electrode slurry has excellent stability, and can improve the rheological properties and coating uniformity of the negative electrode slurry. The various substances on the negative electrode after coating are evenly distributed, which helps to improve the energy density and cycle performance of the battery and ensure the stable performance of the battery during charging and discharging.

[0044] In addition, the rheological properties of the negative electrode slurry are crucial to the coating process. The good uniformity and stability of the slurry means that its rheological properties are more controllable, which can ensure that the slurry can be evenly spread on the current collector during high-speed coating to form an electrode layer with consistent thickness. The uniformity and stability of the slurry also affect the process control and production efficiency of battery manufacturing. By limiting the negative electrode slurry to meet the above requirements, the slurry utilization rate in the battery manufacturing process and the quality and performance consistency of the battery are improved.

[0045] In a second aspect of the present application, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active layer formed by the negative electrode slurry provided in the first aspect.

[0046] The peeling force between the negative electrode current collector and the negative electrode active layer reflects the strength of the bond between the negative electrode current collector and the negative electrode active layer. If the peeling force is too low, it means that the bond between the negative electrode current collector and the negative electrode active layer is not strong, and the active material may fall off during the charge and discharge process of the battery, affecting the performance and life of the battery.

[0047] In some embodiments, the peeling force between the negative electrode current collector and the negative electrode active layer is greater than 1.2 N / m.

[0048] The present application limits the peeling force between the negative electrode current collector and the negative electrode active layer to >1.2N / m, indicating that the bonding between the negative electrode current collector and the negative electrode active layer is firm, which means that there is good bonding between the negative electrode current collector and the negative electrode active layer, and the electrode can maintain structural stability during the battery charge and discharge cycle, reduce the risk of internal short circuit, and extend the service life of the battery.

[0049] In the specific implementation of this application, the test method for the peeling force can adopt a 180° peeling test, also known as a tape peeling test. Specifically, a section of the negative electrode sheet sample after coating and drying is selected, and a strip with a width (such as 10mm) is cut at one end of the sample for pasting the tape. This strip should be perpendicular to the edge of the current collector; a section of standard tape (such as 3M test tape) is pasted to the cut surface of the negative electrode active layer to ensure that the tape is completely bonded and free of bubbles; the end of the sample with the tape is fixed on the peeling force tester, and the instrument pulls the tape from the negative electrode active layer at an angle of 180° and a constant tensile speed (such as 200mm / min) to measure the force required during the peeling process; the test instrument will record the average force required during the peeling process, which is the peeling force.

[0050] The negative electrode current collector has two functional surfaces arranged opposite to each other, and the functional surfaces are used to apply the negative electrode slurry to form a negative electrode active layer. The negative electrode active layer is arranged on both surfaces of the negative electrode current collector. In some embodiments, the thickness of the negative electrode active layer is 60 to 100 μm. The thickness of the negative electrode active layer here refers to the sum of the thicknesses of the negative electrode active layers on the two functional surfaces of the negative electrode current collector.

[0051] In some embodiments, the compaction density of the negative electrode active layer is 1.4 to 1.8 mg / cm 3 The compaction density refers to the amount of active material that can be contained in a unit volume. By limiting the compaction density of the negative electrode active layer to the above range, the active material can be packed more densely, which helps to achieve a higher capacity.

[0052] In some embodiments, the surface density of the negative electrode sheet is 60 to 300 mg / cm 2 . Surface density refers to the mass per unit area of ​​the active material coated on both sides of the negative electrode sheet. By limiting the surface density of the negative electrode sheet within the above range, it is possible to ensure that the energy density of the battery is high enough, optimize the lithium ion transmission path and electronic conductivity, and also help control the expansion of the battery during charging and discharging, reduce stress accumulation during the cycle process, and thus improve the cycle stability of the battery.

[0053] When preparing the negative electrode sheet, the negative electrode active material, conductive agent, binder and dispersant can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. The material of the negative electrode current collector can be at least one of copper foil, nickel foam and copper foam.

[0054] A third aspect of the present application provides a battery, comprising the negative electrode sheet provided in the second aspect.

[0055] Due to the inclusion of the above-mentioned negative electrode sheet, the battery not only has high energy density and excellent cycle performance, but also has excellent charge and discharge performance at a high rate.

[0056] In some embodiments, the battery further includes a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active layer including a positive electrode active material.

[0057] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer arranged on the surface of the positive electrode current collector. The positive electrode active layer includes a positive electrode active material, a second conductive agent and a second binder.

[0058] When preparing the positive electrode sheet, the positive electrode active material, the second conductive agent, and the second binder can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and slitting. In a specific embodiment, the positive electrode active layer includes 70% to 99% of the positive electrode active material, 0.5% to 15% of the second conductive agent, and 0.5% to 15% of the second binder in terms of mass percentage.

[0059] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the second conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the second binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.

[0060] The present application does not limit the specific type of the positive electrode active material in the positive electrode sheet, and it can be a positive electrode active material commonly used in current batteries, such as at least one composite oxide of lithium and metals of cobalt, nickel, manganese and combinations thereof. Specifically, the positive electrode active material includes at least one of lithium cobalt oxide, lithium-rich manganese, nickel-cobalt lithium manganese oxide, lithium manganese oxide, and lithium iron phosphate.

[0061] The battery also includes a diaphragm. The present application does not limit the specific selection of the diaphragm material, and it can be a diaphragm material commonly used in batteries, such as a polypropylene diaphragm, a polyethylene diaphragm, a polypropylene / polyethylene double-layer composite diaphragm, a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer composite diaphragm, etc.

[0062] When preparing the battery, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain the battery cell, and the battery cell is encapsulated in a pre-stamped aluminum-plastic film. After the encapsulated battery is dried to remove moisture, the electrolyte is injected into the dry battery. After the battery is aged, formed and sealed for the second time, the battery preparation is completed.

[0063] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0064] Example 1

[0065] The method for preparing the negative electrode sheet of this embodiment includes:

[0066] The negative electrode active material, binder, conductive agent and dispersant are mixed in a mass ratio of 95%:3.5%:1.0%:0.5%, and 50% of the total mass of water is added and stirred to form a negative electrode slurry, wherein the negative electrode active material is a mixture of graphite and silicon carbon in a mass ratio of 9:1, the binder is polyacrylic acid PAA and styrene-butadiene rubber SBR, the conductive agent is conductive carbon black SP and carbon nanotubes CNT, and the dispersant is castor oil sulfate; the negative electrode slurry is coated on a copper foil current collector with a thickness of 6 μm, and the double-sided coating surface density is 110 g / m 2 After cold pressing and vacuum drying, a negative electrode sheet with a thickness of 77 μm was obtained.

[0067] Example 2

[0068] The difference from Example 1 is that the dispersant is styrene-maleic anhydride.

[0069] Example 3

[0070] The difference from Example 1 is that the dispersant is dodecyl sulfosuccinate.

[0071] Example 4

[0072] The difference from Example 1 is that the dispersant is a compound of castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate in a mass ratio of 4:4:2.

[0073] Example 5

[0074] The difference from Example 1 is that the dispersant is a compound of castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate in a mass ratio of 3:5:2.

[0075] Example 6

[0076] The difference from Example 1 is that the dispersant is a compound of castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate in a mass ratio of 5:3:2.

[0077] Example 7

[0078] The difference from Example 1 is that the dispersant is a compound of castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate in a mass ratio of 5:4:1.

[0079] Example 8

[0080] The difference from Example 1 is that the dispersant is a compound of castor oil sulfate, styrene-maleic anhydride and dodecyl sulfosuccinate in a mass ratio of 3:4:3.

[0081] Example 9

[0082] The difference from Example 1 is that the dispersant is a compound of castor oil sulfate and styrene-maleic anhydride in a mass ratio of 1:1.

[0083] Example 10

[0084] The difference from Example 1 is that the dispersant is a compound of castor oil sulfate and dodecyl sulfosuccinate in a mass ratio of 2:1.

[0085] Embodiment 11

[0086] The difference from Example 1 is that the dispersant is a compound of styrene-maleic anhydride and dodecyl sulfosuccinate in a mass ratio of 2:1.

[0087] Example 12

[0088] The difference from Example 1 is that the dispersant is polyoxyethylene alkyl ether.

[0089] Embodiment 13

[0090] The difference from Example 1 is that the mass ratio of graphite to silicon carbon is 8:2.

[0091] Embodiment 14

[0092] The difference from Example 1 is that the mass ratio of graphite to silicon carbon is 6:4.

[0093] Embodiment 15

[0094] The difference from Example 1 is that the negative electrode active material is graphite.

[0095] Example 16

[0096] The difference from Example 1 is that the negative electrode active material is silicon carbon.

[0097] Comparative Example 1

[0098] The difference from Example 1 is that no dispersant is added to the negative electrode active layer, and the mass ratio of the negative electrode active material, the binder, and the conductive agent is 95.5%:3.5%:1.0%.

[0099] Test example

[0100] 1. Negative electrode slurry performance test

[0101] 1. Viscosity

[0102] The negative electrode slurry was placed in a test cup, and the initial viscosity and the viscosity after standing for 24 hours were tested using a rotational viscometer.

[0103] 2. Test the difference between the solid content of the upper layer and the solid content of the lower layer

[0104] After standing for 24 hours, use a pipette to take the upper 3mm layer of the negative electrode slurry and place it on an empty foil weighing m0. After baking it for 1 minute, weigh m1. The rate of change of the difference between the two is recorded as the upper layer solid content, that is, upper layer solid content = (m0-m1) / m0×100%.

[0105] Use a pipette to take 3 mm of the lower layer of the negative electrode slurry and place it on an empty foil and weigh it m2. Bake it for 1 minute and weigh it m3. The rate of change of the difference between the two is recorded as the solid content of the lower layer, that is, the solid content of the lower layer = (m2-m3) / m2×100%.

[0106] 2. Negative electrode performance test

[0107] Negative electrode stripping force test: Use the 180° stripping method to quantitatively measure the stripping strength. Fold the free end of the negative electrode sheet 180°, clamp the free end of the electrode sheet and the test plate on the upper and lower clamps respectively, and use a tensile testing machine to perform continuous stripping in the same environment until the copper foil current collector and the negative electrode active layer are completely separated, and read the stripping strength value, which is the electrode stripping force.

[0108] 3. Electrochemical performance test

[0109] 1. Cycle stability test

[0110] Large single crystal nickel cobalt lithium manganese oxide (NCM523) is mixed with conductive carbon black and PVDF in a mass ratio of 94:3.0:3.0, dissolved in N-methylpyrrolidone, and the solid content is controlled to be 50% to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil current collector, and after vacuum drying at 95° C., roller pressing, and pressurizing, a positive electrode sheet is obtained;

[0111] The negative electrode sheet, separator and positive electrode sheet of the embodiment and the comparative example are assembled into a lithium-ion battery, and the electrolyte is injected to obtain a soft-pack battery of about 400mAh; wherein the electrolyte is 1mol / L LiPF6 / ethylene carbonate (EC) + propylene carbonate (PC) + diethyl carbonate (DEC) + EMC (volume ratio 1:0.3:1:1), and the separator is a PP / PE / PP three-layer composite separator.

[0112] The above soft pack battery was used to test the cycling performance of the material. It was charged to 4.20V at a constant current of 3C, then charged at a constant voltage, the current was gradually reduced to 0.05C, and then discharged to 2.75V at a discharge rate of 1C. This charge and discharge cycle was repeated 400 times, and the discharge capacity Q1 at the first cycle and the discharge capacity Q400 at the 400th cycle were measured. The 400-week capacity retention rate was calculated according to 400-week capacity retention rate = Q400 / Q1×100%.

[0113] 2. 2C charging constant current ratio

[0114] The above soft pack battery was charged at 25°C with a constant current of 2C to 4.20V, and then charged at a constant voltage with the current gradually reduced to 0.05C. The charging capacity of the 2C charging stage and the total charging capacity of the entire charging process were recorded. The total charging capacity should include the charging capacity of the 2C constant current charging stage and the subsequent constant voltage charging stage.

[0115] The 2C charging constant current ratio can be calculated by the following formula: 2C charging constant current ratio = 2C constant current charging capacity / total charging capacity × 100%.

[0116] 3. Expansion rate test

[0117] The initial thickness d1 of the battery in the test example and the comparative example. The battery is charged to 4.50V at a constant current of 3C at 25°C, then charged to 4.50V at a constant voltage of 0.05C, and then discharged to 3.0V at a discharge rate of 1C. This charge and discharge cycle is repeated 400 times, and the thickness d2 of the battery after 400 cycles is tested. The expansion rate is calculated according to the expansion rate = (d2-d1) / d1×100%.

[0118] 4. Energy density

[0119] Using a battery charge and discharge tester, charge the battery to 4.25V at 0.5C constant current at 25°C, then charge it at constant voltage until the current drops to 0.02C. After standing for 5 minutes, discharge the battery to 2.5V at 0.5C constant current, and record the battery's first discharge capacity Q. 放 and the first discharge energy E 放 , the volume of the measured battery cell is recorded as V, and the battery energy density (Wh / L) = E 放 / V.

[0120] The test results are shown in Table 1 and Table 2.

[0121] Table 1

[0122]

[0123]

[0124] Table 2

[0125]

[0126] According to Table 1 and Table 2, the addition of dispersant can effectively reduce the viscosity of the slurry, slow down the viscosity change, reduce the sedimentation rate, improve the fluidity of the slurry, and make the coating have better leveling. In addition, the addition of dispersant has no significant effect on the charging constant current ratio and cycle performance of the lithium battery, and can effectively improve the processing performance of the anode, improve the uniform stability of the negative electrode slurry, and at the same time improve the energy density of the lithium-ion battery.

[0127] Specifically, the viscosity change fluctuation of the negative electrode slurry of Examples 1 to 16 is small. After standing for 24 hours, the difference between the solid content of the upper layer and the solid content of the lower layer is less than 0.3%, and further ≤0.25%. The pole piece peeling force is ≥1.5N / m. When applied to the battery, the energy density of the battery can be ≥620Wh / L, the 2C charging constant current ratio is ≥74.4%, the 3C / 1C cycle 400T capacity retention rate is ≥85.6%, and the 3C / 1C cycle 400T expansion rate is ≤10.5%.

[0128] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A negative electrode slurry, characterized in that: The negative electrode slurry comprises a negative electrode active material, a conductive agent, a binder and a dispersant; The dispersant includes at least one of dodecyl sulfosuccinate, castor oil sulfate, lauryl sulfate, butyl oleate sulfate, alkyl pyridinium chloride, polyoxyethylene alkyl ether, acetylene glycol, dialkyl sulfosuccinate, polycarboxylate, polymethacrylic acid derivatives, styrene-maleic anhydride, and condensed naphthalene sulfonate.

2. The negative electrode slurry according to claim 1, characterized in that The molecular weight of the alkyl pyridinium chloride is 330-350; the dialkyl sulfosuccinate is selected from sodium dialkyl sulfosuccinate; the polycarboxylate is selected from at least one of sodium polyacrylate, polyethyl methacrylate, and calcium polyacrylate; the polymethacrylic acid derivative is selected from polymethyl methacrylate; the molecular weight of the styrene-maleic anhydride is 10,000-200,000; the condensed naphthalene sulfonate is selected from sodium condensed naphthalene sulfonate; Preferably, the dispersant comprises the castor oil sulfate, the styrene-maleic anhydride and the dodecyl sulfosuccinate, and the mass ratio of the castor oil sulfate, the styrene-maleic anhydride and the dodecyl sulfosuccinate is (3-5): (3~5):(1~3)。 3. The negative electrode slurry according to claim 1 or 2, characterized in that: The negative electrode slurry comprises, by mass content, 91% to 97% of negative electrode active material, 2% to 5% of binder, 0.3% to 3% of conductive agent and 0.1% to 1.5% of dispersant.

4. The negative electrode slurry according to any one of claims 1 to 3, characterized in that: The negative electrode active material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, graphene, silicon oxygen, and silicon carbon; and / or, The binder includes at least one of styrene-butadiene rubber, polyacrylic acid, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, and polyimide; and / or, The conductive agent includes at least one of conductive carbon black, conductive graphite, nano-carbon fiber, carbon nanotube, and graphene; Preferably, the negative electrode active material comprises graphite and silicon carbon, wherein the mass ratio of graphite to silicon carbon is (6-9):(1-4).

5. The negative electrode slurry according to any one of claims 1 to 4, characterized in that: The initial viscosity of the negative electrode slurry is 3000-4500 mPa·s; after the negative electrode slurry is left standing for 24 hours at 25° C. and an ambient humidity of ≤25%, the viscosity is 5000-9000 mPa·s, and the difference between the solid content of the upper layer and the solid content of the lower layer is less than 0.3%.

6. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active layer formed by the negative electrode slurry according to any one of claims 1 to 5.

7. The negative electrode sheet according to claim 6, characterized in that: The peeling force between the negative electrode current collector and the negative electrode active layer is greater than 1.2 N / m.

8. The negative electrode sheet according to claim 6 or 7, characterized in that: The thickness of the negative electrode active layer is 60 to 100 μm; and / or, The compaction density of the negative electrode active layer is 1.4 to 1.8 mg / cm 3 and / or, The surface density of the negative electrode sheet is 60 to 300 mg / cm 2 .

9. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 6 to 8.

10. The battery according to claim 9, characterized in that The battery also includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode active layer containing a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide, lithium-rich manganese, lithium nickel cobalt manganese oxide, lithium manganese oxide, and lithium iron phosphate.

Citation Information

Patent Citations

  • Conductive agent dispersion liquid, electrode slurry, electrode, battery, and preparation methods thereof

    CN101752548A

  • Lithium ion battery anode, preparation method of lithium ion battery anode and lithium ion battery

    CN107732150A

  • Low-temperature lithium ion battery and preparing method thereof

    CN109286008A

  • Solid cleaning composition

    CN111788287A

  • Negative electrode slurry, negative electrode plate as well as preparation methods and applications thereof

    CN112201481A